The effect of an electronic monitoring device with audiovisual reminder function on adherence to inhaled corticosteroids and school attendance in children with asthma: a randomised controlled trial. Issue 3 (March 2015) - Chan, Amy H Y; Stewart, Alistair W; Harrison, Jeff; Camargo, Carlos A; Black, Peter N; Mitchell, Edwin A
Summary: Background: Suboptimum adherence to preventive asthma treatment is associated with substantial morbidity and mortality, yet adherence often remains poor. We aimed to investigate whether use of an inhaler with audiovisual reminders leads to improved adherence and asthma outcomes in school-aged children who presented to the emergency department with an asthma exacerbation. Methods: We did a randomised controlled trial in patients aged 6–15 years who attended the regional emergency department in Auckland, New Zealand with an asthma exacerbation and were on regular inhaled corticosteroids. Using a simple, unrestricted block randomisation with block sizes of 200, we randomly assigned patients to receive an electronic monitoring device for use with their preventer inhaler with the audiovisual reminder functions either enabled to support adherence to inhaled corticosteroids (intervention group) or disabled (control group). Participants were followed up every 2 months for 6 months. The primary outcomes were adherence to preventive inhaled corticosteroids and number of days absent from school for any reason. Asthma control was assessed as a secondary outcome. All analyses were done in the intention-to-treat population. This trial is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12613001353785. Findings: The study took place between May 10, 2010, and Feb 26, 2012. We randomly assigned 220 patients, 110 to the intervention group and 110 to the control group. Median percentage adherence was 84% (10th percentile 54%, 90th percentile 96%) in the intervention group, compared with 30% (8%, 68%) in the control group (p<0·0001). The proportion of days absent from school for any reason was 1·9% (10th percentile 0·0%, 90th percentile 7·9%) in the intervention group and 1·7% (0·0%, 8·6%) in the control group. The change in asthma morbidity score from baseline to 6 months was significantly greater in the intervention group than in the control group (p=0·008), with a reduction of 2·0 points from a mean baseline score of 9·3 (SD 2·2) to 7·3 (2·1) in the intervention group, compared with a reduction of 1·2 points from a baseline of 9·2 (2·5) to 8·0 (2·2) in the control group. Interpretation: Use of an electronic monitoring device with an audiovisual reminder led to significant improvements in adherence to inhaled corticosteroids in school-aged children with asthma. This intervention could be beneficial for the improvement of asthma control in patients for whom poor asthma control is related to poor adherence. Funding: Health Research Council of New Zealand and Cure Kids.